The Evolution of Learning in Higher Education Polytechnic Institutions: The ACADIGIA Case-Study - Andrei Ternauciuc; Diana Andone; Vlad Mihaescu; Silviu Vert; Manuel Salvador Gomes Araújo (Ubiquity Proceedings, 2024)
This paper conducts an in-depth examination of the transformative journey in learning paradigms within higher education polytechnic institutions. Utilizing a case study approach, we trace the evolutionary trajectory of pedagogical practices and technological integration in the context of transitioning from in person to online classes. By exploring the experiences of the ACADIGIA Consortium, the driving force behind the Erasmus+ project with the same name, we aim to provide useful insights into the challenges faced and strategies employed during the evolution and implementation of the ACADIGIA transformation. The diversity of experience provided by the partners, from academia as well as from industry, and from the cultural backgrounds of Portugal, Spain, Romania, Italy, Greece, and Ireland, represents one of the strengths of this endeavor as well as one of its main challenges. The findings contribute to a broader understanding of the dynamic nature of higher education in polytechnic settings, shedding light on effective approaches to enhance the quality and relevance of learning experiences in an ever-changing educational landscape. This paper can serve as a valuable resource for educators, administrators, and policymakers seeking evidence-based guidance in navigating the evolving terrain of higher education polytechnic institutions.